Risk of autoimmunity, cancer seeding, and adverse events in human trials of whole-tissue autologous therapeutic vaccines - Garrett Gianneschi; Anthony Scolpino; James Oleske (Cancer Pathogenesis and Therapy)
Background: Whole-tissue autologous therapeutic vaccines (WATVs) are a form of cancer immunotherapy that use a patient's own pathological tissue. Concerns exist regarding the potential of WATVs to induce autoimmunity or the spread of cancer; however, their adverse events (AEs) have not been adequately studied. This literature review primarily aimed to evaluate the risks of autoimmunity and cancer seeding associated with using WATVs in human clinical trials. Its secondary objectives included assessing the incidence of AEs graded 1–5 using the Common Terminology Criteria for Adverse Events v5.0. Methods: The inclusion criteria were any clinical trial using human subjects in which at least part of the cancer vaccine was derived from the patient's own tumor tissue, which likely preserved the unique tumor-associated antigens (TAAs) present in the patient's tumor (i.e., whole-tissue). Tumor vaccine trials that used limited TAAs or highly processed tumor antigens were excluded. Published clinical trials were searched using Google Scholar until March 2024. The authors elaborated on the risk of bias in such cases, as indicated. All reviewed publications were searched for evidence of autoimmunity, cancer seeding, and other AEs. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 statement guided the review. Results: Data from 55 human clinical trials, abstracts, case reports, and unpublished data were analyzed, including 3323 patients treated with WATVs for various cancers. The primary outcomes were: (1) no documented cases of WATV-induced autoimmunity, (2) no documented cases of WATV-induced spreading or seeding of noninfectious cancers, and (3) the observed 0.24% (2/838) risk of spreading or seeding infectious cancers was attributed to inadequate sterilization. The secondary outcomes were: (1) no deaths were attributed to WATV therapy, (2) 0.18% (6/3323) incidence of grade 4 AEs, (3) 0.42% (14/3323) incidence of grade 3 AEs, (4) the incidence of grades 1–2 AEs was 52.21% (478/916). Conclusions: WATVs carry no risk of inducing autoimmunity and essentially no risk of cancer seeding if properly sterilized. WATVs also exhibit a side effect profile comparable to that of routine vaccinations, with common, mild, and transient adverse effects. The combined risk of grade 3 and 4 AEs was 0.60% (20/3323). No deaths were causally associated with WATV treatment.